Optimisasi Desain dan Kinerja Alat Kupas Kulit Polong Kacang Tanah yang Portable - Yohanes, Yohanes Benediktus Yokasing; Amiruddin Abdullah; Alexius Leonardo Johanis; Fransiskus Sapar; Aditya Christian Putra Mandala; James Evan Leha (Politeknik Negeri Jakarta, 2025)
The peeling machine for peanut shells, which has limitations and achieves a peeling capacity of only 85%, requires optimization. To this end, the friction, pressure, and gravity involved are analyzed. The design concept of the peeling machine considers the topographic conditions, particularly in the East Nusa Tenggara (NTT) region. The result of this optimization produces the 'Peeling Machine for Peanut Shells.' The resulting peeling machine has the following specifications: height of 700 mm, length of 50 mm, width of 37 mm, operated manually, with a production capacity of approximately 0.86 ounces per second. The performance, in terms of rotation speed and the number of peeled peanuts, shows a significant correlation with increased capacity. Increasing the diameter of the blades also contributes to higher output. At a speed of 60 rpm, a closer blade distance (11 mm) yields the best results, indicating that the optimization of machine design needs to consider the blade distance in relation to the rotation speed to enhance efficiency.